Status Ahli Waris Janda Terhadap Hak Penerima Testamen - Saharuddin Saharuddin (Jurnal Litigasi Amsir, 2022)
Saharuddin,Status of the Widow's Heirs Against the Rights of Testament RecipientsThis study uses a normative research type with a statute approach. Types of sources of primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study indicate that the widow in inheriting the abintestato is the same as the position of the child, both are classified into group 1 (one). While in testamentair inheritance the position of a widow (wife) is not the same as that of a child, this is because the child has its own absolute share while the widow (wife) does not have its own absolute rights. Regarding the part that the widow (wife) gets, it lies in the number of statements left by the heir, the more testaments, the less or none at all received by the widow (wife).